PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP KINERJA KEUANGAN (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2013-2014) - Kusdiyanto Kusdiyanto; Dezy Dwi Kusumaningrum (Benefit: Jurnal Manajemen dan Bisnis, 2015)
This research is to understand and to analyze the influence of good corporate governance and leverage toward financial performance on Manufacture Corporation registered in BEI year 2012-2013, both partially and simultaneously. Indicator used to explain good corporate governance in this research is including board of directors, independent directors and audit committee.Analysis method used in this research is doubled-linier regression in accordance to the purpose of this research which is to analyze the influence of independent variable toward dependent variable. Sample used in this research is all Manufacture Corporations registered in BEI year 2012-2013. The determination of sample is using purposive sampling. By using this method, it acquired 92 corporations that will be used as the sample in this research. The result of hypothesis test in this research shows that board of director do not affect significantly toward financial performance. Independent director significantly has negative impact toward financial performance. Audit committee significantly has positive impact toward financial performance. Leverage significantly has negative impact toward financial performance.